Evaluation of immune response to Bacillus subtilis spores expressing Clonorchis sinensis serpin3. Issue 10 (14th September 2020) - Lin, Zhipeng; Sun, Hengchang; Ma, Yan; Zhou, Xinyi; Jiang, Hongye; Wang, Xi; Song, Jiaman; Tang, Zeli; Bian, Qing; Zhang, Zhen; Huang, Yan; Yu, Xinbing
Abstract: Clonorchis sinensis ( C. sinensis ) is one of the most serious food-borne parasites, which can lead to liver fibrosis or cholangiocarcinoma. Effective measures for clonorchiasis prevention are still urgently needed. Bacillus subtilis ( B. subtilis ) is an effective antigen delivery platform for oral vaccines. Chonorchis sinensis serpin (CsSerpin) was proved to be potential vaccine candidates. In this study, CsSerpin3 was displayed on the surface of B. subtilis spore and recombinant spores were orally administrated to BALB/C mice. CsSerpin3-specific IgA levels in faecal, bile and intestinal mucous increased at 4–8 weeks after the first administration compared with those in control groups. The mucus production and the number of goblet cells in intestinal mucosa elevated in B.s- CotC-CsSerpin3 (CotC, coat protein of B. subtilis spore) spores treated group compared to those in blank control. No significant difference in the activities of glutamic-pyruvic transaminase/ alanine aminotransferase and glutamic oxalacetic transaminase/aspartate aminotransferase were observed between groups. There was no side effect inflammation and observable pathological damage in the liver tissue of mice after administration. Moreover, collagen deposition and Ishak score were statistically reduced in B.s- CotC-CsSerpin3 spores treated mice. In conclusion, B. subtilis spores displaying CsSerpin3 could be investigated further as an oral vaccine against clonorchiasis.